Laser Coherence Meter Based on Nanostructured Liquid Crystals - A. Anczykowska; S. Bartkiewicz; J. Mysliwiec (International Journal of Optics)
We present the method for coherence length measurement using coherence meter based on hybrid liquid crystal structures doped with gold nanoparticles. The results indicate that the method is able to determine the coherence length of coherent light sources with precision of 0.01 m at wavelength range from 200 to 800 nm for wide range of initial beam powers starting from 1 mW. Given the increasing use of laser technology in industry, military, or medicine, our research may open up a possible route for the development of improved techniques of coherent diagnostic light sources.